Exploring the Interplay Between Environmental Design and Management Practices and Their Association with Crime at Multi-Unit Apartments - Deryol, Rustu (American journal of criminal justice, 2025)
The present study builds upon Newman and Franck‘s (1982) classic work by examining whether and how the actions of managers can mediate the effects of physical design features on crime. The present study also examines possible interactions between management practices and physical design features of apartments. These interactions are explored through structural equational modeling of site observation and manager survey data from a Cincinnati-based sample of 237 apartments. Our findings indicate that physical design features do not have significant indirect effects on crime counts via management practices, with the exception of the effect of amenities, which partially operates through secured access. Another important finding to emerge from the study involved moderation effect models showing that regulatory signs conditioned the association between dead-end/cul-de-sac and property and all crime counts. Finally, secured access at cul-de-sac locations corresponded with less violent and all crime counts compared to cul-de-sac locations without secured access. The results of this study imply that future studies examining the relationship between environmental design, place management, and crime might consider hybrid theoretical models, further exploring design-management interaction effects.